A prospective randomised study of dense Infinity cytological brush versus regularly used brush in pancreaticobiliary malignancy. (3rd May 2016) - Kylänpää, Leena; Boyd, Sonja; Ristimäki, Ari; Lindström, Outi; Udd, Marianne; Halttunen, Jorma
Abstract: Background and study aims Endoscopic retrograde cholangiopancreatography (ERCP) with a cytological sample is a valuable tool in the diagnosis of the aetiology of biliary stricture. Our aim was to evaluate whether a more dense Infinity® cytological brush is more sensitive in diagnosing malignancy than the regularly used brush.Patients and methods We recruited 60 patients with a biliary stricture suspicious for malignancy for a randomised controlled trial. Patients were randomly assigned to an Infinity® brush group ( n  = 30) and a regularly used cytology brush group ( n  = 30). All the patients had verified cancer during follow-up.Results Crossing the brush over the stricture was possible in each case without dilatation of the biliary duct. Brush cytology yield was good or excellent in 86.7% of cases with the Infinity® brush and 96.7% with the regular brush ( p  = 0.161). The cytological sample showed clear malignancy in three patients (10.0%) in the Infinity® group and in 12 (40.0%) patients of the regular brush group ( p  = 0.007). The cytological diagnosis was highly suspicious for malignancy or malignant in 14 patients (46.7%) in the Infinity® group and in 23 patients (76.7%) in the regular brush group ( p  = 0.017). The result was benign in 10 patients (33.3%) in the Infinity® group and in four patients (13.6%) in the regular brush group ( p  = 0.067).Conclusions With the standardised technique, the sensitivity of brush cytology is fairly good. The dense Infinity® brush does not show any advantage regarding sensitivity compared with the conventional cytology brush.